Porcine SLITRK1: Molecular cloning and characterization. Issue 1 (7th October 2014) - Larsen, Knud; Momeni, Jamal; Farajzadeh, Leila; Bendixen, Christian
Abstract : The membrane protein SLITRK1 functions as a developmentally regulated stimulator of neurite outgrowth and variants in this gene have been implicated in Tourette syndrome. In the current study we have cloned and characterized the porcine SLITRK1 gene. The genomic organization of SLITRK1 lacks introns, as does its human and mouse counterparts. RT‐PCR cloning revealed two SLITRK1 transcripts: a full‐length mRNA and a transcript variant that results in a truncated protein. The encoded SLITRK1 protein, consisting of 695 amino acids, displays a very high homology to human SLITRK1 (99%). The porcine SLITRK1 gene is expressed exclusively in brain tissues. Abstract : Molecular cloning of the porcine SLITRK1 gene is reported. A SLITRK1 transcript variant encoding a truncated protein was identified. The SLITRK1 transcript was exclusively expressed in brain tissues. There was low methylation of both the SLITRK1 gene body and its promoter. SLITRK1 was mapped to pig chromosome 11.